POLITICAL RIGHTS AND FREEDOMS OF PEOPLE AND CITIZEN ARE MODERN CONSISTING AND PROBLEMS OF REALIZATION IN UKRAINE - Липчук, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In article the problem of realization of political rights and freedoms of man and citizen in Ukraine. The main immediate problems of modern Ukrainian society related to the defense of the rights and freedoms of man and citizen. A most effective ways to address and eliminate the consequences of these problems and the causes of their manifestation, impacts on the realization and protection of rights in Ukraine.